Effect of Conventional Cataract Surgery and Femtosecond Laser-Assisted Cataract Surgery on Bruch's Membrane Opening-Minimum Rim Width, Retinal Nerve Fiber Layer, and Macular Thickness. (7th February 2023) - Reñones, Josefina; Anton, Alfonso; Gonzalez-Martin, Jesús María; Carreras, Humberto; Loro-Ferrer, Juan Francisco
Abstract : Purpose . To evaluate the effect of conventional cataract surgery (CCS) and femtosecond laser-assisted cataract surgery (FLACS) on Bruch's membrane opening-minimum rim width (BMO-MRW), peripapillary retinal nerve fiber layer thickness (RNFL), and macular thickness (MT) using spectral-domain optical coherence tomography (SD-OCT). Methods . BMO-MRW, RNFL, and MT were measured using SD-OCT preoperatively, 1 month and 6 months after surgery in both CCS and FLACS groups. Differences between preoperative and postoperative values were evaluated in both groups. The postoperative changes were evaluated in each group and compared between groups. Results . A total of 146 eyes of 146 patients were included in this study, 65 underwent CCS, and 81 underwent FLACS. One month after surgery, there was an increase (in microns) of 20.93 in BMO-MRW, 4.26 in RNFL, and 7.85 in MT in CCS group (P < 0.001 ), and 17.7, 3.73, and 5.65, respectively, in FLACS group (P < 0.001 ). Six months after surgery, there was an increase of 12.53 in BMO-MRW, 1.42 in RNFL, and 4.72 in MT in CCS group (P < 0.001 ), and 13.7, 1.88, and 4.14, respectively, in FLACS group (P < 0.001 ). The postoperative changes in CCS group were similar to those in FLACS group. Conclusion . CCS as well as FLACS result in a slight increase in BMO-MRW, RNFL, and MT values one month and six months after surgery. Neither CCS nor FLACS lead to a deterioration in the parameters that define the structure of the optic nerve head and the macula. These results suggest that FLACS is as safe as CCS regarding the optic nerve head and the macula in normal eyes.